2020
DOI: 10.1136/tsaco-2020-000520
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet therapy is associated with a high rate of intracranial hemorrhage in patients with head injuries

Abstract: BackgroundAntiplatelet agents are increasingly used in cardiovascular treatment. Limited research has been performed into risks of acute and delayed traumatic intracranial hemorrhage (ICH) in these patients who sustain head injuries. Our goal was to assess the overall odds and identify factors associated with ICH in patients on antiplatelet therapy.MethodsA retrospective observational study was conducted at two level I trauma centers. Adult patients with head injuries on antiplatelet agents were enrolled from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The present study’s relatively low incidence of TICH in ACT-patients has been reported by several other studies in the past years [ 1 , 15 20 ]. Even though one-third of the ACT-patients in the present study were on VKAs and not DOACs, the TICH-incidence did not differ significantly from the TICH-incidence in the cohort of patients with ground-level traumas not on ACT or APT.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The present study’s relatively low incidence of TICH in ACT-patients has been reported by several other studies in the past years [ 1 , 15 20 ]. Even though one-third of the ACT-patients in the present study were on VKAs and not DOACs, the TICH-incidence did not differ significantly from the TICH-incidence in the cohort of patients with ground-level traumas not on ACT or APT.…”
Section: Discussionsupporting
confidence: 78%
“…Even though one-third of the ACT-patients in the present study were on VKAs and not DOACs, the TICH-incidence did not differ significantly from the TICH-incidence in the cohort of patients with ground-level traumas not on ACT or APT. Given the state of current research where VKA has shown higher TICH-incidence compared to DOAC, it is possible that the TICH-incidence would be even lower in this subgroup in a population where VKAs were less frequent [ 1 , 15 , 16 ]. If the RR of 1.78 for APT-patients can be properly demonstrated in a study with sufficient sample size, there is a substantial TICH-hazard for APT-patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendation 13: the risk of bleeding needs to be assessed before initiating antiplatelet therapy in patients with trauma-induced hypercoagulopathy complicated by arterial thrombosis Antiplatelet drugs inhibit cyclooxygenase (COX)-1, P2Y12 receptor, phosphodiesterase (PDE), or GPIIb/IIIa. This class of drugs is the first-line treatment for arterial thrombosis, but it can also increase bleeding risk in trauma patients [100]. Therefore, any antiplatelet therapy should only be planned after careful assessment of the bleeding risk in patients with trauma-induced hypercoagulopathy complicated by arterial thrombosis.…”
Section: Recommendation 11: Reducing Stress and Tissue Damage Are Prerequisites For Improving Trauma-induced Hypercoagulopathymentioning
confidence: 99%
“…Among older patients, this platelet‐associated TBI coagulopathy is usually attributed to antiplatelet therapy and co‐morbidities, 11,12 and the use of any form of anticoagulant may exclude patients from studies of TBI coagulopathy 8,13 . In addition, normal platelet counts have been shown to decrease after age 50 years, 14 potentially increasing mortality risk for older adults presenting with TBI.…”
Section: Introductionmentioning
confidence: 99%